Managers' characteristics: Results from an exploratory comparison of young managers in Bulgaria and USA and its implications for management education in Bulgaria - Nils-Erik Aaby; Marin A. Marinov; Svetla Trifonova Marinova (Journal for East European Management Studies, 1997)
This paper explores managerial characteristics of young Bulgarian and U.S. managers by identifying differences between the two samples in terms of risk taking, reliance on others, leadership style, use of intelligence and cooperation. A number of reasons accounting for significant differences are discussed, suggestions for the content and approaches to management education in Bulgaria are presented. – – Der vorliegende Artikel untersucht charakteristiken von jungen Managern in Bulgarien und den USA. Unterschiede zwischen den beiden Gruppen in Bezug auf Risikobereitschaft, Abhängigkeit von anderen, Führungsstil, Einsatz von Intelligenz und Kooperationsverhalten werden untersucht. Eine Reihe von Gründen die für signifikante Unterschiede sprechen werden diskutiert. Darüber hinaus werden Vorschläge für mögliche Ansätze und Inhalte einer Managerausbildung in Bulgarien vorgestellt.
Keywords: 650